Occupational Health Risks and Comprehensive Management Strategies for E-Commerce Live Streamers - Mirza, Muhammad Navis; Oktaviana (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
The rapid growth of e-commerce has made live streaming a vital marketing tool for real-time engagement with consumers. However, the profession comes with distinct occupational health risks. This paper investigates the physical, biological, ergonomic, psychosocial, and chemical risks they face, such as disrupted circadian rhythms, voice strain, and mental health pressures.. This study addresses the specific health challenges of e-commerce live streamers and proposes strategies to improve their well-being. A community service project, using a qualitative approach, was implemented to support live streamers through educational workshops, personalized consultations, and community-building activities. A literature review identified physical, biological, ergonomic, psychosocial, and chemical hazards. The program, with 193 participants, raised awareness of health risks and resulted in positive behavioral changes, such as improved ergonomic practices and mental health management. Participants reported enhanced well-being and better work-life balance, though challenges like time constraints and limited consultation resources were noted.To mitigate these risks, industry stakeholders should prioritize health interventions, including ergonomic adjustments and mental health support. Future research should evaluate the long-term impact of these interventions and establish policies to safeguard the health and productivity of live streamers.